Maternal Caesarean Outcomes Following Sublingual Misoprostol as an Adjunctive Intraoperative Uterotonic - Ozori, Stanley Ebiogbo; Julius, Obilahi-Abhulimem Thomas; McFubara, Kalada Godson; Michael, Mbah Kanayochukwu; Gordon, Atemie; Justina, Usman Malgwi; Solomon, Warisuo Ariwelo (Journal of Advances in Medical and Pharmaceutical Sciences, 2025)
Background: This study was aimed at evaluating the safety of adjunctive sublingual misoprostol in reducing intraoperative blood loss during caesarean section, with the objectives of determining the need for additional intraoperative oxytocic, need for postoperative blood transfusion and the side effect profile of the study medications when adjunctive sublingually administered misoprostol is used in preventing excessive blood loss at caesarean delivery. Methods: This study involved one hundred and fifty-two gravidae at term, who were randomised into two trial arms (Misoprostol study arm or the Placebo study arm), having met the inclusion criteria and were scheduled for caesarean section. The misoprostol group received 400-ug of sublingual misoprostol. The control group received two sublingual placebo tablets. Both arms received 30 IU intravenous oxytocin. The primary outcome measure was the need for extra doses of oxytocic. The secondary outcome measures were the need for postoperative blood transfusion and side effect profile of the study medication. A P value =.05 was statistically significant. Results: The sublingual misoprostol study arm had a lesser need to receive more oxytocics than the sublingual placebo study arm (11.8% vs 19.7%), but this was not statistically significant (P = .18). The requirement for blood infusion was not statistically significant between the trial arms (P = .78), although fewer women were transfused in the misoprostol arm than in the placebo arm of the study (9.2% vs 10.5%). All cases of shivering were seen in the misoprostol group (88.2%), and this was statistically significant between the study groups, (P = .00). Conclusion: Sublingually administered adjunctive misoprostol at a dose of 400 ug at caesarean birth did not considerably decrease the demand for extra doses of ecbolics, and blood transfusion following the surgery, but caused significant shivering.